New Generalized Measures of Fuzzy Entropy and Their Properties - Parkash, Om; Gandhi, C. P. (Journal of Informatics and Mathematical Sciences, 2011)
Fuzziness is one of the universal attributes of human thinking and objective things whereas fuzzy set theory is one of the efficient means of researching and processing fuzzy phenomena in real world. Taking this fact into consideration, we have introduced and investigated two new generalized fuzzy measures of entropy and studied their essential and desirable properties.